Dysregulation of Ki-67 Expression in T Cells of Children with Autism Spectrum Disorder - Khaled Alhosaini; Mushtaq A. Ansari; Ahmed Nadeem; Sabry M. Attia; Saleh A. Bakheet; Laila Y. Al-Ayadhi; Hafiz M. Mahmood; Haneen A. Al-Mazroua; Sheikh F. Ahmad (MDPI AG, 2021)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by behavioral abnormalities such as impairments in social function and deficits in communication. The etiology of autism is unknown in most cases, but many studies have pointed towards the immune system as a causative agent in autism. Specific studies implicated lymphocytes, natural killer (NK) cells, monocytes, cytokines, and specific transcription factors in the development of ASD. The protein Ki-67 is n expressed in the proliferating cells and is used as a tool in several disorders. Ki-67 plays a crucial role in many neurological diseases. However, Ki-67 role in ASD is not fully understood. In this study, we investigated the possible role of Ki-67 expression in autistic children. We compared Ki-67 production in CD3+, CD4+, CD8+, CXCR4+, CXCR7+, CD45R+, HLA-DR+, GATA3+, Helios+, and FOXP3+ peripheral blood mononuclear cells (PBMCs) in autistic children to typically developing (TD) controls using immunofluorescence staining. We also determined Ki-67 mRNA levels in PBMCs using RT-PCR. The results revealed that autistic children had significantly increased numbers of CD3+Ki-67+, CD4+Ki-67+, CD8+Ki-67+, CXCR4+Ki-67+, CXCR7+Ki-67+, CD45R+Ki-67+, HLA-DR+Ki-67+, CXCR4+GATA3+, GATA3+Ki-67+ cells and decreased Helios+Ki-67+ and FOXP3+Ki-67+ cells compared with TD controls. In addition, the autistic children showed upregulation of Ki-67 mRNA levels compared with TD controls. Further studies need to be carried out to assess the exact role of Ki-67 and its therapeutic potential in ASD.